Influence of weather factors on male Spodoptera litura (Fab.) moth catches in pheromone traps in the groundnut ecosystem: Influence of weather factors on male Spodoptera litura (Fab.) moth catches in pheromone traps in the groundnut ecosystem - ROHINI SUGANDI; KOLLI BHARGHAVI; BASAVARAJ YENAGI; P NAGARAJU; MOTAGI BN (Journal of Oilseeds Research, 2023)
A regular field monitoring was done since five years at AICRP on Groundnut, MARS, Dharwad, Karnataka during Kharif &rabi/summer (2017 to 2021). In nutshell, the highest and lowest moths collected/trap were in Kharif-2021 and Kharif-2019 respectively. Collections were more in Kharif compared to rabi. Overall, the highest trap catches were in the month of July & August. The minimum temperature, relative humidity and rainfall had a positive correlation with the moth trapping, while the maximum temperature had a negative correlation. Pheromone traps can be used an effective tool in IPM to assess population fluctuations and forewarn the needy.